Official policy and the impact on financial innovations in the Caribbean - Zephirin, Mary (Caribbean Centre for Monetary Studies [St. Augustine]TT, 1996)
Considers the transmission mechanisms of monetary policy in open economies. Discusses how financial innovations could affect the effectiveness of the transmission channels. Looks at descriptions of monetary policy in the Caribbean and at some of the innovations documented in Caribbean markets to assess how these may be expected to impact on monetary policy.